(untitled) (Colombia Medica, 1989)
A preliminary report from a 20% sample of referred patients to the Hospital Universitario del Valle (HUV) in Cali, Colombia, from October 1987 to March 1988 showed that among the ten leading causes of reference, 70% were classified as obstetric and gynecological in origin. This finding motivated a revision of the total of referrals to this service during June 1988. In this period, the HUV arrived at 708 patients, from which 95.6% of them were living in the Departamento del Valle, and 96% came from urban areas; 82.6% were permanent and were classified as emergencies with a fatality rate of 42 per thousand. Approximately 96% of the referral sheets were answered in writing during the ten following days. It was found that 18.8% of those references belonged to a maximal level of medical attention (tertiary care level), 38% to the secondary level, and 40% to the primary care level. Deliveries, considered as usual, accounted for 54% of the total number of cases, and 84% of the surgical procedures were cesarean sections. This operation is classified as an activity that can be performed at the secondary level except for abruptio placentae or due to high obstetric risk.